2008
DOI: 10.1177/1352458508089688
|View full text |Cite
|
Sign up to set email alerts
|

Use of health care services and satisfaction with care in people with multiple sclerosis in Stockholm County: A population-based study

Abstract: The great majority of PwMS use hospital specialist care and primary care in parallel, with many departments and services involved. Better accessibility of certain services, for example, psychosocial counseling and rehabilitation, and other improvements, for example efforts to provide coordinated and comprehensive care for PwMS may increase satisfaction with care and should be the focus of scientific evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 40 publications
13
54
0
Order By: Relevance
“…The Stockholm MS Study found a high frequency (approximately 70%) of reliance on others for activities of daily living, consistent with the results reported here. 4 A detailed analysis of activities of daily living from the Stockholm study identified some of the same problems with activities of daily living found in the present study, including in the areas of heavy housework, shopping, and cooking. Transportation outside the home also figured prominently among problematic areas in that study.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The Stockholm MS Study found a high frequency (approximately 70%) of reliance on others for activities of daily living, consistent with the results reported here. 4 A detailed analysis of activities of daily living from the Stockholm study identified some of the same problems with activities of daily living found in the present study, including in the areas of heavy housework, shopping, and cooking. Transportation outside the home also figured prominently among problematic areas in that study.…”
Section: Discussionsupporting
confidence: 70%
“…3 Another was the Stockholm MS Study, which found a high frequency (70%) of reliance on others for activities of daily living. 4 The Stockholm study identified several specific problem areas for people with MS: heavy housework, shopping, and cooking. Transportation outside the home also figured prominently among areas of concern.…”
mentioning
confidence: 99%
“…This is supported by a study in Sweden, in which 166 MS patients were questioned about their satisfaction with their MS treatment. In general, patients were satisfied with their management, except for a lack of access to rehabilitation and psychosocial counselling services [29]. In a further study [30] patients were offered 75 proposals for improvements in MS services, in an attempt to identify the 10 most important areas for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][24][25][26] The present review focused explicitly on studies that incorporated the patient's perceptions about their health care and, specifically, on studies in which detailed interview-based information was provided. The review framework, based on three temporal phases of health care, provided a person-centered perspective on barriers to access and utilization of health-care services.…”
Section: 18mentioning
confidence: 99%